A comparison of DNA and immunoblot fingerprinting of the SII biotype of coagulase negative staphylococci. - Burnie, J. P. (Cambridge University Press, 1988)
Thirty-eight isolates of the SII biotype of coagulase negative staphylococci were examined by phase typing, antibiograms, DNA and immunoblot fingerprinting. Multiple isolates were available from 5 patients with clinically proven infections and from 12 further patients who were epidemiologically distinct. Only 3 of the isolates were phage typable and antibiograms produced only 9 types. All isolates were typable by both DNA and immunoblot fingerprinting and reproducibility was excellent provided the conditions were standardized. Discrimination was better with immunoblot fingerprinting (17 types) than DNA fingerprinting (11 types). Both techniques were successful in assessing the significance of multiple isolates from a single patient.